2021
DOI: 10.1590/1981-5271v45.3-20210082.ing
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring experience in medical residency: challenges and experiences

Abstract: Introduction: Medical residency represents a challenging moment, with a high level of demand and the need to develop several personal and professional skills. Therefore, in April 2019, the unprecedented mentoring program for thirty internal medicine residents was implemented, seeking to offer personal support and encourage professional development. Experience Report: A mentoring program was structured in April 2019, lasting 11 months, consisting of 30 internal medicine residents and 6 mentors with experience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…A randomised controlled study of junior doctors showed that mentoring provided them with a supportive community that helped them professionally and well as personally. 10 , 32 It positively impacted stress, morale, job satisfaction and wellbeing. 32 Belonging to a team and connecting with others in the workplace addresses a core need for team members and makes them feel valued and supported.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A randomised controlled study of junior doctors showed that mentoring provided them with a supportive community that helped them professionally and well as personally. 10 , 32 It positively impacted stress, morale, job satisfaction and wellbeing. 32 Belonging to a team and connecting with others in the workplace addresses a core need for team members and makes them feel valued and supported.…”
Section: Discussionmentioning
confidence: 97%
“… 9 One clear advantage to mentoring is that it can facilitate development in aspects not often included in formal training, such as wellbeing, life balance, empathy and relationship management. 10 , 11 Mentoring has also been found to improve confidence and stress management, encourage critical reflection, and improve connections with colleagues through networking. 9 , 11 Nurse mentoring programs also have the potential to sustainably strengthen the nursing workforce.…”
Section: Introductionmentioning
confidence: 99%